The Long Way to Emancipation in Margaret Laurence’s A Jest of God - Varela-Zapata, Jesús (Canada and Beyond: A Journal of Canadian Literary and Cultural Studies, 2024)
Lauren Berlant’s critical stance proves instrumental to carry out the analysis of Margaret Laurence’s A Jest of God, a story dealing with personal insecurities and crises, related to feelings of loss, trauma, suffering or failure. There is no doubt that Rachel, the protagonist and first-person narrator, encompasses all the trappings around the notion of “cruel optimism,” and the novel can be considered as a drama of adjustment, where the fantasies of the “good life” are interweaved with the suffocation of ordinary life. Rachel will have to dismantle the view that by being both a good citizen and a loving daughter she may achieve happiness or, at least, peace of mind. This story of personal struggle and emancipation can be eventually related to the political circumstances in Canada’s long process towards autonomy and independence.